1972
DOI: 10.1002/eji.1830020406
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide can substitute for helper cells in the antibody response in vitro

Abstract: The effect of lipopolysaccharide (LPS) from E. coli on the primary and the secondary antibody response against sheep red blood cells (SRC) by spleen cells in vifro was studied. LPS, which is a non-specific mitogen for B cells, often caused an increased antibody response. Stimulation was obtained on day 4 of the culture if the spleen cells gave a low response t o SRC without LPS, whereas n o stimulation was obtained if the antibody response was high. However, kinetic studies showed that cultures treated with LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

1973
1973
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(49 citation statements)
references
References 32 publications
4
45
0
Order By: Relevance
“…The addition of Fc fragments to the SRBC cultures does not alter the kinetics of the response. This observation agrees with those previously published (35), which show that when SRBC are added to LPS-treated spleen cell cultures, the anti-SRBC response is higher than in those cultures receiving only SRBC, but the overall kinetics of the response remain unaltered in the presence of LPS.…”
Section: Potentiation Of Antibody Responses By Fc Fragmentssupporting
confidence: 93%
“…The addition of Fc fragments to the SRBC cultures does not alter the kinetics of the response. This observation agrees with those previously published (35), which show that when SRBC are added to LPS-treated spleen cell cultures, the anti-SRBC response is higher than in those cultures receiving only SRBC, but the overall kinetics of the response remain unaltered in the presence of LPS.…”
Section: Potentiation Of Antibody Responses By Fc Fragmentssupporting
confidence: 93%
“…During the preparation of this manuscript, Hammarstrom and Smith (17) reported the same results indicating the mitogenic and polyclonal antibody-producing effects of nystatin on murine B-cell cultures. All these findings concerning nystatin are in good agreement with the properties reported on B-cell mitogens, such as LPS, S III, POL and so on (4,10,15,34,36). Since all thymus-independent antigens have been reported to be B-cell mitogens (4), it should be determined in the future if nystatin is a thymus-independent antigen.…”
Section: Methodssupporting
confidence: 81%
“…The mechanism by which the observed antibody response occurred would seem to be best explained by the ability of LPS to bypass the normal T-cell helper function. Such an effect in the antibody production to T-dependent antigens has been previously demonstrated both in vivo or in vitro with antigens such as heterologous erythrocytes (6)(7)(8), haptens (9,10), and with the antigen used in the present studies, namely HGG (11). In this regard, perhaps the most convincing data is that obtained by Watson et al (10), who showed that the spleens of congenitally athymic mice (B cells only) could be induced to form antibody in vitro to a hapten free of any carrier molecule when the culture was supplemented with LPS.…”
Section: Discussionmentioning
confidence: 83%